Reliability Analysis of Distribution Network Based on Reliability Index Assessment Method, A Case Study - Zailani, Putri; Lomi, Abraham; Nurcahyo, Eko (Department of Electrical Engineering, National Institute of Technology Malang - INDONESIA, 2017)
A  primary  requirement  of  a  modern  electric power system is reasonable ability to satisfy the customer load requirements. Electric utilities involve generation, transmission, and distribution facilities each one of which contributes its own inherent  difficulties  to  the  problem  of  satisfying  customer requirement. A power system should be designed and expanded the facilities  in  order to  perform  its  intended function  with a reasonable risk. With increasing the electrical energy demand and the potential of disruption that may occur in the system, the distribution  system  must  have  high  reliability  and  continues supply to customer. In this case, the reliability of the distribution system needs to be evaluated by monitoring and analyzing the level of distribution system failure in a certain period of time.  A study  on  a  practical  distribution  system  with  application  of automatic  circuit  reclosers  (ACRs)  which  plays  an  important role in enhancing the reliability index of system is presented. The reliability index assessment analyze the reliability index of the existing system before and after application of ACRs. From the simulation  point  of  view,  the  system  average  interruption frequency  index  (SAIFI)  is  about  19.43%  or  decreased  the failure frequent event from 11.4 failure/ customer.year to 9.25 failure/customer.year);  while  the  momentary  average interruption frequency index (MAIFI) has decreased from 6.72 failure/customer.year to 5.05 failure/ customer.year, or increase the reliability index of about 24.85%.